"Semantic Changes of Words": Causes and Consequences of Some Instances When Semantic Changes Occur in Thai Words, Considering a Comparison Between the New Meaning and the Original Meaning - Khotchaphet, Suwatchai; Preechapongkij, Rattanachai (Ratchaphruek Journal, 2024)
The semantics of a word are a part of language that can change, as words do not possess only a single meaning, leading to the emergence of new meanings when compared to the original ones. This article presents two points: 1) the causes of semantic changes, and 2) some consequences of such changes in the Thai language, considering a comparison between the new and original meanings. The causes of semantic changes derive from six factors: 1) linguistic reasons, 2) historical and scientific progress, 3) social factors, 4) psychological reasons, 5) influence from foreign languages, and 6) the necessity for new terms. As for the consequences of semantic changes, there are two aspects: 1) effects on the scope of semantic changes, which include narrowing and broadening of meanings, influenced by temporal factors. Furthermore, the scope of semantic changes also expands through comparative usage, termed "metaphorical extension", and 2) effects on the evaluation of semantic changes, which include positive and negative changes, especially negative changes resulting from words becoming impolite or worse than before, potentially leading to these words becoming taboo.